Aplikasi Penjualan Jam Tangan Secara Online Studi Kasus: Toko JAMBORESHOP - Rahmat Hidayat (Universitas Bina Sarana Informatika, 2017)
Abstract— Internet as a global network has been shown to facilities the wearer in both the communication and the exchange of information. In this case the internet is a medium that is most appropriate information to answer all needs, which can be accesses by the public whenever and wherever. The design of information system web-based sales watches is selling watches based e-commerce, while generation the maximum profit for the sale of the maximum required anyway. So, it needs a marketing medium, such as for example the E-commerce. E-commerce website creating using text editor sublime is one of the solutions to solve existing problems, especially in matters of increasing sales and introducing products to consumers quickly and without having to go to the consumer. Given that it is expected the authors were able to help introduce E-commerce in order to assist the IT lovers, or people who want to know about E-commerce.